Assessment of Restorative Skills for Amalgam Restoration - Jagruti Nanda1 , Lora Mishra2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dental treatment procedures are mostly governed by factors such as biocompatibility of restorative materials,patients demand for esthetics and conservative approach for the minimal loss of tooth structure. GV Blackfollowed ‘EXTENTION FOR PREVENTION’ for restorative treatment which follows classical cavity formsand principles which almost remained unchanged and unchallenged for 50years using amalgam. Though itrequired uniform depth, ease of manipulation and excessive tooth structure damage for proper retentionof it. The support from clinical observation of success and failures of different restorations has presentedwith the concept of new designs. This article reviews the literature on assessing and evaluation of amalgamrestoration. Information on the characteristic material, its rate of progress with time and its nature of theassociation. Mainly focusing on the relationship between the deterioration of amalgam restoration and riskof secondary caries.